Comunicación familiar en el proceso de revelación de la orientación sexual de hijos gays e hijas lesbianas - Rueda-Toro, Juan (2024)
Analyze the elements of family communication associated with the coming out process of sexual orientation. Qualitative research with narrative design by topics. A content analysis of 12 interviews with three gay sons, three lesbian daughters and 6 mothers was done. Intrafamilial, contextual, and intrapsychic contents of communication were related to gender stereotypes, education, family support, religion, self-discovery, and acceptance. The assertive style dominated, although the passive and aggressive style were common before and during the disclosure. The strategies were divided into direct and indirect verbal and non-verbal. The contents of the communication are transformed with the disclosure process, while the styles and strategies seek to reestablish the homeostasis of the families.